The good Samaritan strikes again - McManus, Patrick F. (H. Holt, 1992)
Gathering together twenty-four of his hilarious essays<U+2015>originally published in such magazines as Outdoor Life<U+2015>this volume features not only McManus<U+2019>s follies with Mother Nature, but those of human nature as he shares such funny moments of his life as his first kiss, his public relations career, his less than helpful attempt to be a good Samaritan to an injured motorist, and so much more.